Strengthening Character in the National Plus Curriculum: Its Advantages and Challenges - Niken Ismia Dewi (EXOUSIA : Jurnal Pendidikan Agama Kristen, 2022)
The 21st century is the century of information, computing, automation, and communication. Education must adapt to the era of that developing century, in particular the curriculum applied in schools. This study aims to describe the comparison of the application of the National Curriculum and the National Plus Curriculum. This research is a qualitative research with a phenomenological approach. The study was conducted at the Kasih Bapa Christian Elementary School, limited to respondents and research subjects related to the implementation of the curriculum in class VI which amounted to two classes, namely VI a and VI b, each of which amounted to 20 people. The number of teachers for class VI from several subjects of the study as respondents at Kasih Bapa Christian Primary School was seven. From the research that has been carried out, it was found that a form of comparison of the application of the national curriculum and the national plus curriculum on character education in class VI of Kasih Bapa Christian Elementary School, namely: First, the national curriculum based on character education leads to the challenges of the 21st century while the national curriculum plus with integrated character-based Bibles starts from the school's vision; Secondly, the national curriculum directs subjects to sub-themes while the national plus curriculum is more directed towards the introduction of the Creator who creates in an orderly manner; Third, the purpose of the national curriculum is to be able to answer the challenges of changing times while the national plus curriculum can answer the challenges of the 21st century if done consistently; Fourth, the characters achieved by the national Curriculum are only a few according to the assessment of each lesson while the characters produced by the national plus curriculum are the whole in the Bible